PENGARUH ENDORSEMENT DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA DI MASA PANDEMI COVID-19 - Mursyidah, Mursyidah; Rusdiana, Rusdiana; Malihah, Lola (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
This study aims to determine effect of endorsement and brand awareness on student purchasing decisions during the COVID-19 pandemic. Field research with a quantitative approach. Population this study were students of the Faculty of Islamic Economics and Business, using purposive sampling. Sample results used as many as 75 samples. Based results is no partial endorsement effect (X1) on purchasing decisions (Y). Meanwhile, results of (partial) T test showed Sig. = 0.002 < α = 0.10 and T count = 3.206 > T table = 1.666. It is concluded is a partial influence of brand awareness (X2) on purchasing decisions (Y). Based on results the endorsement variable (X1) and brand awareness (X2) simultaneously influence purchase decision (Y).. Endorsement variable (X1) and brand awareness variable (X2) can explain variation of dependent variable of 33.9%. While the remaining 66.1% is influenced by other variables outside of this study.